ChemInform Abstract: Synthesis of Highly Substituted Isocoumarins by Rhodium‐Catalyzed Annulation of Readily Available Benzoic Acids. Issue 41 (19th September 2013) - Unoh, Yuto; Hirano, Koji; Satoh, Tetsuya; Miura, Masahiro
Abstract Rhodium‐catalyzed oxidative coupling of benzoic acid (I) with alkynes provides isocoumarin derivatives.